Lincoln on Race and Slavery - Lincoln, Abraham, 1809-1865 (Book collections on Project MUSE., 2009)
Henry Louis Gates, Jr., presents the full range of Lincoln's views, gathered from his private letters, speeches, official documents, and even race jokes, arranged chronologically from the late 1830s to the 1860s. --from publisher description.